A commented translation of Hans Richter's early work "The isotropic law of elasticity". (August 2019) - Graban, Kai; Schweickert, Eva; Martin, Robert J.; Neff, Patrizio
We provide a faithful translation of Hans Richter's important 1948 paper "Das isotrope Elastizitätsgesetz" from its original German version into English. Our introduction summarizes Richter's achievements.